A Rare Culprit of Simultaneous Arteriovenous Thromboembolism: Acute Viral Perimyocarditis - Christoph Sossou; Tobi Ogundare; Ogechukwu Chika-Nwosuh; Amee Sodha; Christopher Nnaoma; Cynthia McKinney; Jose Bustillo (Case Reports in Cardiology)
Simultaneous arteriovenous embolism is extremely rare. Herein, we present a rare case of systemic arteriovenous emboli in a healthy 33-year-old male after an episode of acute viral perimyocarditis. The culprits are postulated to be viral-induced myocardial necrosis and resulting proinflammatory state in the setting of negative malignant, autoimmune, genetics, and chronic infectious conditions. The patient was successfully managed with guideline-directed medical therapy and safely discharged to a subacute rehabilitation facility.